العناصر اللغوية ودورها في تحقيق التماسك النصي في قصة تحت المظلّة لنجيب محفوظ - الحجوج, محمد عبد الرحمان (Revues faculté des lettres et des langues; Vol. 1 No 21 (2017): مجلة كلية الآداب و اللغات, 2018)
Abstract: This study aims at analysing Najeeb Mahfuz' story ' tahat al mathalah' in the light of the text, and discovering the textual cohesion . At first sight, the story seems to be as a disconnected sentence and sometimes unrelated. Rapid glimpses may not be understood that portrait the non- seriousness of life and the absence of events. This is the main motive behind selecting this story. After a profound study of the story, away from sentence structure, the aim is to achieve a comprehensive linguistic analysis, that is text structure. In the light of linguistic and non linguistic studies and elements of the cohesion in the text, it has been noticed that the story represents a well connected literary text cohesion. at the beginning , the technical and literary elements of the story were exposed in such a way that does help know the textual cohesion elements, Keeping in mind the non linguistic elements related to the external environments surrounding the text. الملخص تهدف هذه الدراسة إلى قراءة قصة (تحت المظلة) لنجيب محفوظ وتحليلها في ضوء نحو النص، واستكشاف مظاهر التماسك النصي فيها، حيث تبدو القصة للوهلة الأولى عبارة عن جملة غير مترابطة تظهر أحداثاً منفصلة، ولقطات سريعة غير مفهومة تصور عبثية الحياة، ويغيب فيها زمن أحداثها، وهذا هو الدافع في اختيارها، ولكن بعد القراءة المتعمقة، وتجاوز حدود البنية اللغوية للجملة إلى بنية لغوية أكبر وأشمل للتحليل اللغوي وهي بنية النص، وفي ضوء الدراسات اللسانية للنص، ودراسة عناصر التماسك النصي المتمثلة في السياق اللغوي وغير اللغوي ، تبيّن أن القصة تمثل نصاً أدبياً متماسكاً ومترابطاً. وقبل ذلك تعرضت في المهاد للجانب الأدبي الفني المتعلق بعناصر القصة ؛ لأن ذلك يُسعف في معرفة  عناصر التماسك النصي، لا سيما العناصر غير اللغوية المتعلقة بالظروف الخارجية المحيطة بالنص.